Manajemen Pembelajaran Inklusi di TK Laboratori Pedagogia UNY Yogyakarta - Fitriani, Laily (ACIECE, 2019)
This article uses the type of descriptive qualitative research. this study describes the management of learning used in Kindergarten Laboratori Pedagogia UNY Yogyakarta. This kindergarten is one of the institutions that carry out inclusion based on culture, this study aims to describe the management of inclusive learning in Kindergarten Laboratori Pedagogia UNY Yogyakarta namely Javanese methods, with the object of research is inclusion learning used in Pedagogia Kindergarten and the principal of the Pedagogia Laboratories Kindergarten UNY Yogyakarta. For data collection, technical data analysis uses the interactive model of qualitative data analysis techniques with tho stages namely, data reduction and data display. The results of this study found that in the learning process not too distinguished between normal children and children with special needs. There are several points which are distinguished, one of which is the level of success of the learning process